BURDEN OF PROVING WORK ABSENCE IN OVERTIME WAGE CLAIMS - Hardila; Miharja, Marjan (JILPR Journal Indonesia Law and Policy Review, 2026)
The appointment of Acting Regional Heads in Indonesia is regulated by Minister of Home Affairs Regulation Number 4 of 2023, which is a response to the need to maintain continuity of regional government during the transition period leading up to the implementation of simultaneous regional elections. This regulation outlines the mechanism for appointing Acting Regional Heads, which involves a proposal from the Minister of Home Affairs to the President for Acting Governors, and from the Governor to the Minister of Home Affairs for Acting Regents/Mayors. Criteria that must be met by acting candidates include being from high-ranking officials at the middle or pratama levels. In the context of simultaneous regional elections, the appointment of Acting Regional Heads must take into account aspects of neutrality and independence. Acting Regional Heads are required to refrain from engaging in practical political activities, not using state facilities to support certain candidates, and not making significant changes to the bureaucratic structure that could affect the neutrality of the State Civil Apparatus (ASN). Strict monitoring and reporting mechanisms are implemented to ensure that Acting Regional Heads carry out their duties with integrity and transparency. The implementation of this regulation aims to ensure that the simultaneous regional elections process runs fairly and democratically, without any intervention that could undermine public confidence in the election results. The Acting Regional Head plays a key role in maintaining the stability of regional government during the transition period, as well as supporting the implementation of regional elections that are free from fraud and violations.